ACUTE DERMAL IRRITATION TEST OF SIMPLISIA BUNGA GUMITIR OINTMENT ON ALBINO RABBIT - Wayan Sangi Vani; I Made Merdana; I Wayan Gorda (Fakultas Kedokteran Hewan Universitas Udayana, 2025)
Marigold (Tagetes erecta L.) are widely cultivated for ornamental purposes and also as a natural food coloring. Gumitir flowers contain antioxidants, secondary metabolites such as terpenoids, essential oils, flavonoids, and carotenoids. This study aims to determine the results of the acute dermal irritation test of the simplicia flower gumitir ointment on albino rabbits, referring to The OECD Guideline for Testing of Chemicals - No. Test: 404, Acute Dermal Irritation/Corrosion (OECD) 2015. The test animals, consisting of three albino rabbits (Oryctolagus cuniculus), were treated with the simplicia flower gumitir ointment, with a placebo (negative control) as a comparison, using the patch test technique and evaluation based on the Amanded Draize test. The research results show that the application of gumitir flower simplicia ointment does not cause erythema and edema, both in the treatment and control groups, with a Mean Irritation Index of 0.16. Observation of reversibility effects showed the growth of fine and normal hair around the test area. It can be concluded that the gumitir flower simplicia ointment is non-irritating and therefore safe to use. It is recommended to conduct further tests as an effort to improve the salve made from gumitir flower simplicia, including salve formulation, stability testing, safety testing, and a review of previous test data.